A handbook of ethical practice : a practical guide to dealing with ethical issues in information and library work - McMenemy, David; Burton, Paul F., 1947-; Poulter, Alan.; ScienceDirect eBooks (Oxford [England] : Chandos Publishing, 2007)
This book looks at all of the ethical issues facing information and library professionals in one overarching, and practically-focused, text. As such, it is of great benefit to both practitioners and to LIS students. The focus of the book is two-fold: (1) It contains a detailed discussion of the issues that impact on the day-today practice of information workers in the 21st century; and (2) contains case studies discussing potential solutions to ethical problems faced. The book provides sections which work like flowcharts leading from ethical issues through decision points to proposed solutions based on the literature/case studies. This is a highly useful resource that provides appropriate access to potential solutions for day-to-day queries.
A taxonomy of the ethics of information use -- The librarian and ethics -- Ethical codes: an international overview -- The ethics of information supply: from selection to provision -- Intellectual property questions -- Freedom of access, privacy and acceptable use -- Ethical management of the self, the individual and the organisation -- Conclusion: ethical futures.
Includes bibliographical references and index.
Elsevier
Keywords: Information science -- Moral and ethical aspects; Library science -- Moral and ethical aspects; BUSINESS & ECONOMICS -- Business Ethics; Information science -- Moral and ethical aspects; Library science -- Moral and ethical aspects; Electronic books